The Impact of Intellectual Capital and Cultural Intelligence on Innovation and Performance, with Knowledge Sharing as a Mediator in Manufacturing Companies. - Yuwono, Wisnu; Tjan, Charles; Kesumahati, Erilia (Program Sarjana Manajemen Universitas Internasional Batam, 2024)
Batam City has become a popular destination for individuals from outside the city seeking employment due to the numerous manufacturing companies established there, both from local and foreign sources. The success of these companies is influenced not only by the abilities of their workforce but also by how well employees adapt to their working environment. This study aims to explore whether intellectual capital and cultural intelligence impact innovation and performance within the manufacturing sector in Batam City, with knowledge sharing serving as a mediating variable for cultural intelligence. Utilizing a quantitative research approach, the study is supported by primary data collected through surveys in the form of questionnaires. The researchers employed SPSS and Smart PLS software to analyze variable data and test the hypotheses. The findings reveal the following: 1) intellectual capital has no effect on innovation., 2) intellectual capital positively affects performance. 3) cultural intelligence positively affects innovation., 4) cultural intelligence positively affects knowledge sharing. 5) knowledge sharing positively affects innovation., 6) innovation positevely affecs on performance, and 7) cultural intelligence affects innovation through knowledge sharing as a mediating variable. In relation to these results, this research is recommended as a reference for managers in improving innovation and performance